2016
DOI: 10.1093/beheco/arw091
|View full text |Cite
|
Sign up to set email alerts
|

Beak color dynamically signals changes in fasting status and parasite loads in king penguins

Abstract: Dynamic ornamental signals that vary over minutes, hours or weeks can yield continuous information on individual condition (e.g., energy reserves or immune status), and may therefore be under strong social and/or sexual selection. In vertebrates, the coloration of the integument is often viewed as a dynamic ornament, which in birds can be apparent in the beak. King penguins (Aptenodytes patagonicus) are monomorphic seabirds that possess conspicuous yellow-orange (YO) and ultraviolet (UV) beak spots that are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…68–69 in Jouventin & Dobson, ). Our previous studies have shown that the color of right and left ornaments is similar (repeatable) (Schull et al, , ), and those ornaments thus likely convey similar information. Sex‐dependent lateralization may thus allow penguins pairs to benefit from not having to learn how to coordinate their behavior across multiple breeding seasons, as the direction of lateralization of successive mates should be similar.…”
Section: Discussionmentioning
confidence: 82%
“…68–69 in Jouventin & Dobson, ). Our previous studies have shown that the color of right and left ornaments is similar (repeatable) (Schull et al, , ), and those ornaments thus likely convey similar information. Sex‐dependent lateralization may thus allow penguins pairs to benefit from not having to learn how to coordinate their behavior across multiple breeding seasons, as the direction of lateralization of successive mates should be similar.…”
Section: Discussionmentioning
confidence: 82%
“…However, colour parameters of the beak in King Penguins have been shown to vary seasonally and depend on the fasting status and parasite load (Schull et al . ). Thus, such a dynamic signal might be inapt to encode individual or sex information.…”
Section: Discussionmentioning
confidence: 97%
“…Further, the color of yellow breast feathers (also containing the endogenously synthetized pterin pigment) has been related to innate immunity (Nolan, Dobson, Dresp, & Jouventin, ), suggesting that genes involved in the production of that specific pigment may also be linked to the immune system. There is also support for links between ornament colors and various condition indices, including body size and condition, stress status, and metabolic rate (Keddar, Couchoux, Jouventin, & Dobson, ; Schull et al., ; Viblanc et al., ) (see Table ). Finally, the beak spot ornament is a dynamic signal, reflecting short‐ to medium‐term physiological changes in parasite loads and fasting status (Schull et al., ).…”
Section: Introductionmentioning
confidence: 98%
“…There is also support for links between ornament colors and various condition indices, including body size and condition, stress status, and metabolic rate (Keddar, Couchoux, Jouventin, & Dobson, ; Schull et al., ; Viblanc et al., ) (see Table ). Finally, the beak spot ornament is a dynamic signal, reflecting short‐ to medium‐term physiological changes in parasite loads and fasting status (Schull et al., ). However, experimental studies are now required to test whether trait production (i.e., beak spot and auricular patch coloration and size) is condition‐dependent.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation